2017
DOI: 10.1007/s00268-017-3906-x
|View full text |Cite
|
Sign up to set email alerts
|

Fine‐Needle Aspiration Cytology (FNAC) in Breast Cancer: A Reappraisal Based on Retrospective Review of 698 Cases

Abstract: FNAC is a reliable tool for diagnosing cancer in suspicious breast lesions with a good sensitivity and PPV in hands of an experienced cytopathologist. Surgical treatment may be safely undertaken based on FNAC particularly in early operable breast cancers suitable for breast conservation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 32 publications
0
25
0
3
Order By: Relevance
“…According to the literature, it represents the first and most useful diagnostic tool in the evaluation of several body lesions. In fact, among the others, it has demonstrated interesting results in terms of diagnostic accuracy in head and neck cancer, breast carcinoma, and cervical carcinoma . To date, only 2 studies, from the same institution, have been published on the diagnostic utility of ultrasound with guided FNAC in the assessment metastatic lymph node disease in vulvar carcinoma.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…According to the literature, it represents the first and most useful diagnostic tool in the evaluation of several body lesions. In fact, among the others, it has demonstrated interesting results in terms of diagnostic accuracy in head and neck cancer, breast carcinoma, and cervical carcinoma . To date, only 2 studies, from the same institution, have been published on the diagnostic utility of ultrasound with guided FNAC in the assessment metastatic lymph node disease in vulvar carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, among the others, it has demonstrated interesting results in terms of diagnostic accuracy in head and neck cancer, breast carcinoma, and cervical carcinoma. [10][11][12][13][14] To date, only 2 studies, from the same institution, have been published on the diagnostic utility of ultrasound with guided FNAC in the assessment metastatic lymph node disease in vulvar carcinoma. Moskovic et al, in their pilot study on 21 patients with early vulvar carcinoma using ultrasound and FNAC, confirmed an overall sensitivity of 83% and specificity of 82% for the detection of groin lymph node metastases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The most common diagnosis using FNAC in the case of the breast is fibro-adenoma followed by fibrocystic disease, breast abscess, chronic inflammatory conditions and suspicious malignant masses [3]. 90-98% of sensitivity is achieved by using FNAC in clinically palpable breast lesions which gives a definitive diagnosis in 95% cases [5,6].…”
Section: Introductionmentioning
confidence: 99%